Selective Estrogen Receptor Modulator Effects of Epimedium Extracts on Breast Cancer and Uterine Growth in Nude Mice - Indran, Inthrani Raja; Zhang, Shi-Jun; Zhang, Zhi Wei; Sun, Feng; Gong, Yinhan; Wang, Xiaochong; Li, Jun; Erdelmeier, Clemens A. J.; Koch, Egon; Yong, Eu Leong (Planta Medica, 2014)
Epimedium is popularly used in traditional Chinese medicine to treat sexual dysfunction, menstrual irregularity, and osteoporosis. The estrogenic effects of the prenylated flavonoids of Epimedium make it an attractive alternative for hormone replacement therapy. Here, we examined the therapeutic potential of the estrogenic herb extract of Epimedium brevicornum as an alternative to hormone replacement therapy in a breast cancer mouse model. To that end, athymic and ovariectomized female nude mice were subcutaneously injected into the mammary fat pads with MCF-7 breast cancer cells, randomly grouped and fed with soy-free feeds, alone or in combination with ethinyl estradiol or different doses of the estrogenic herb extract of E. brevicornum. Our findings demonstrate that unlike ethinyl estradiol, it did not promote the growth of breast cancer xenograft volume and weight, with the highest dose showing a significant reduction in growth and ERα protein content. Moreover, the extract increased uterine weight at the lowest dose, while higher doses had no effects. Put together, our data shows for the first time that despite the estrogenic activity of E. brevicornum, its action is largely tissue specific and dose-dependent. Our data on E. brevicornum presents in vivo evidence for its selective estrogen receptor modulator effect and warrants exploration of its use as an alternative to hormone replacement therapy in menopausal women.
Keywords: Epimedium brevicornum; Berberidaceae; menopause; selective estrogen receptor regulator; breast cancer